Abbott Elementary. The complete third season [videorecording (DVD)] - Brunson, Quinta (Warner Bros., 2025)
It's the season for change for the teachers of Abbott Elementary. Janine leads ambitious growth initiatives for the school while navigating personal and professional challenges. Gregory embraces his role as the "cool" teacher. Ava surprises with moments of unexpected leadership. From Career Day to a heartfelt end-of-year celebration, the Abbott staff prove that with teamwork-and Janine's relentless drive-they can handle anything.